Expected effects of climate change on the animal production in Yemen – A review - Amad, Abdulkarim Abdulmageed; Zentek, Jurgen (Journal of agricultural, environmental and veterinary sciences, 2022)
This study aimed at provide an overview of the effects of climate change on the efficiency of animal productivity and feed resources, and their health, as well as the extent to which animal production in Yemen is affected by this phenomenon (climate change). Climate change is one of the greatest challenges facing the planet today, with adverse effects expected throughout the world and in all aspects of life and to varying degrees. The climate change would be affecting the agricultural systems (plant and animal) in general and particularly the agricultural systems in arid and semi-arid regions, due to gradual changes in increasing of concentration of greenhouse gases in the atmosphere, the global warming, rising sea and ocean levels, as well as with severe changes in precipitation, floods, hurricanes and droughts. According to scientific predictions, the Earth’s surface temperature can rise between 1.8 and 4 ° C by 2100. When the temperature rises between 1.5 and 2.5 ° C, about 20 to 30% of the plant and animal species are expected to be extinct and this will hurt the food security in developing countries. High temperatures resulting from climate change also directly affect the productivity, growth, reproduction and health of livestock, negative impact on reproductive efficiency of males and females and increase and diversity of diseases that affect the productivity. On the other hand, the high temperature resulting from climate change will directly affect the availability of feed resources (natural pasture and feed) for animals, which are important factors for production. As mentioned in the conclusions, Yemen is highly exposed to factors related to climate change, such as high temperatures, droughts, severe floods, agricultural pests, changes in rainfall, and an increase in the frequency and intensity of storms. Climate change will have a negative impact on animal life and productivity directly, affecting food security and employment for large numbers of people.